PROTOTYPE MONITORING AREA PARKIR MOBIL BERBASIS ARDUINO UNO UNTUK MENDETEKSI KETERSEDIAAN SLOT PARKIR SECARA OTOMATIS - Endang Sunandar; Asep Saefullah; Yudha Qirana Meka (CCIT Journal, 2017)
Process monitoring conventional parking area is currently still using manual way to know the number and availability of existing capacity in the parking area, the monitoring process carried out in several ways such as recording the number of vehicles entering and see firsthand the state of the vehicle that was parked. The conventional method is certainly cause some problems for both the parking attendant and the owner of the vehicle, where these obstacles include the difficulty to obtain accurate information about the number of parking slots are available as well as difficult to know where to position the parking slot. Automatic parking monitoring system uses a microcontroller arduino uno as a data processor which utilizes multiple types of sensors are placed at some point areas, where the use of these sensors function as an input device that later processed with output an instruction to the servo motor and also the appearance of an information on an LCD screen that displays information about the number of parking slots are available as well as the location of the parking slot. In addition to using the LCD, the tool is also equipped with two indicator lights that show the status of the parking area and a buzzer will sound as a form of notification to the officer and the owner of the vehicle that the state of the car parking area has full.